PENGARUH FRAUD HEXAGON TERHADAP KECURANGAN LAPORAN KEUANGAN PERUSAHAAN SEKTOR BARANG KONSUMSI PRIMER (CONSUMER NON-CYCLICALS) YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Annisa Nurhasanah; Sulastiningsih Sulastiningsih (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study aims to analyze the influence of components in the fraud hexagon model on financial statement fraud. The method used is quantitative, utilizing secondary data from issuers listed on the Indonesia Stock Exchange for the period 2022 to 2024. A sample of 162 entities was selected using purposive sampling. The results of the analysis indicate that the elements of pressure, opportunity, justification, and collusion have a significant effect on financial reporting fraud practices, while the aspects of capability and arrogant attitude do not show a meaningful impact.